KOMPOSISI HASIL TANGKAPAN GOMBANG DI DESA MESKOM KECAMATAN BENGKALIS KABUPATEN BENGKALIS PROVINSI RIAU - Rani Khairunnisa; Irwandy Syofyan Syofyan; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             One of the fishing gear used by fisherman in Meskom Village is the gombang fishing gear. The purpose of this study is to know the composition of the catch gombang in Meskom Village. The research was conducted in March 2017. Using survey method and descriptive analysis. During the study obtained the total catches of 39,355.4 gr and 508,157 individu with an average 1,405.5 gr and 18,148.5 individu. The dominan catch during the study was the pepai shrimp (Mysis sp) individu about 9,530 gr and 134,760 individu which happened on the third day.  Keywords: Meskom Village, Gombang, Composition and Catch Result